Hemophagocytic Lymphohistiocytosis Complicating Erythroleukemia in a Child with Monosomy 7: A Case Report and Review of the Literature - Samin Alavi; Maryam Ebadi; Alireza Jenabzadeh; M. T. Arzanian; Sh. Shamsian (Case Reports in Hematology)
Herein, the first case of childhood erythrophagocytosis following chemotherapy for erythroleukemia in a child with monosomy 7 is reported. A 5-year-old boy presented with anemia, thrombocytopenia, and hepatosplenomegaly in whom erythroleukemia was diagnosed. Prolonged pancytopenia accompanied by persistent fever and huge splenomegaly and hepatomegaly became evident after 2 courses of chemotherapy. On bone marrow aspiration, macrophages phagocytosing erythroid precursors were observed and the diagnosis of HLH was established; additionally, monosomy 7 was detected on bone marrow cytogenetic examination. In conclusion, monosomy 7 can lead to erythrophagocytosis associated with erythroid leukemia and should be considered among the chromosomal abnormalities contributing to the association.